Thermometry of diogenites - Mukherjee,Amalbikash; Viswanath,T.A. (1987)
P(論文) Mg-Fe^<2+> exchange reaction between orthopyroxene and spinel has been calibrated thermodynamically and empirically and applied to the thermometry of diogenites. Based on regression of the orthopyroxene-spinel Mg-Fe^<2+> distribution coefficients against the Cr-mole fractions of the spinel of a number of naturally and experimentally equilibrated samples, the empirical calibration is more successful, gives internally consistent results and agrees well with independent temperature estimates of a wide range of terrestrial test samples. Uncertainty of the empirically determined temperatures, however, increases with decreasing Mg-Fe^<2+> distribution coefficient between orthopyroxene and spinel and increasing Cr-content of the spinel. Applied to a number of diogenites, the empirical calibration gives moderately high temperatures (687 and 885℃) for the Johnstown and Yamato-75032 diogenites and very high temperatures (between 1512 and 1941℃) for Y-692,-74013 and -74136 diogenites. The Johnstown and Y-75032 diogenites possibly represent thermally equilibrated orthopyroxene-spinel assemblages comparable to slowly cooled terrestrial ultramafic plutonic bodies broadly in the 700-900℃ temperature regime. The higher temperature Yamato group on the other hand appears to be disequilibrium assemblages, affected by shock-reheating, partial melting and recrystallization. departmental bulletin paper